2018
DOI: 10.1016/j.jmig.2017.08.647
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Outcome of MiniArc Single-Incision Sling Used in the Treatment of Primary Urodynamic Stress Incontinence

Abstract: MiniArc maintains its effectiveness and safety in treatment of USI through 5 years with high objective and subjective cure rates and low incidence of complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
13
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 27 publications
3
13
2
Order By: Relevance
“…Similar to our study, other trials reported that questionnaire scores slightly get worse in the medium-term following the expected and natural decline in the efficacy of reconstructive pelvic floor surgeries observed throughout the time. 26,30 In relation to complications, the rates of tape exposure (4.9% in each group) and lower urinary tract symptoms including de novo urgency (12.2% in SIMS and 4.9% in TOT groups) were in accordance to the other reports. [31][32][33][34] A nonsignificant trend towards higher rates of repeat continence surgery was noted in the SIMS group compared to TOT (10.1% and 3.3%, respectively).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Similar to our study, other trials reported that questionnaire scores slightly get worse in the medium-term following the expected and natural decline in the efficacy of reconstructive pelvic floor surgeries observed throughout the time. 26,30 In relation to complications, the rates of tape exposure (4.9% in each group) and lower urinary tract symptoms including de novo urgency (12.2% in SIMS and 4.9% in TOT groups) were in accordance to the other reports. [31][32][33][34] A nonsignificant trend towards higher rates of repeat continence surgery was noted in the SIMS group compared to TOT (10.1% and 3.3%, respectively).…”
Section: Discussionsupporting
confidence: 88%
“…Few studies have reported medium-term outcomes of SIMS. [25][26][27] Overall, the various analyses of our trial demonstrated that objective cure of SUI favored TOT over a SIMS technique in the medium-term. Considering only the participants who completed 3-year follow-up which would best reproduce the treatment differences, cure reached 90.2% for TOT confirming the high success rate for MUS described by literature [21][22][23][24] while SIMS reached 68.3%.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations